2020
DOI: 10.20870/oeno-one.2020.54.4.2553
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock and harvest season affect the chemical composition and sensory analysis of grapes and wines of the Alicante Bouschet (<i>Vitis vinifera</i> L.) grown in a tropical semi-arid climate in Brazil

Abstract: Aim: In this study, we aimed to evaluate the composition of grapes and wines of the Alicante Bouschet variety from a tropical semi-arid area in Brazil, by studying two rootstocks and harvests in different semesters (climates) of the same year.Methods, Results: Vines of Vitis vinifera L., Alicante Bouschet, a teinturier variety, were grown in a tropical semi-arid climate in Brazil. The phenolic composition of the grapes and wines was measured to assess how they had been affected by two rootstocks (IAC 572 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This demonstrated that a stressful environment with less light and more rain increased the effect of rootstocks on berry anthocyanin concentrations and the proper use of rootstock was significant for the scion to adapt to the stressful survival environment. Oliveira et al (2020) used IAC 572 and 1103P to graft Alicante Bouschet, and it was found that rootstock and year had a synergy effect, and year had a greater effect on flavonoid compound concentrations. A similar discovery was made on Syrah.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated that a stressful environment with less light and more rain increased the effect of rootstocks on berry anthocyanin concentrations and the proper use of rootstock was significant for the scion to adapt to the stressful survival environment. Oliveira et al (2020) used IAC 572 and 1103P to graft Alicante Bouschet, and it was found that rootstock and year had a synergy effect, and year had a greater effect on flavonoid compound concentrations. A similar discovery was made on Syrah.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed that rootstocks did affect the flavonoid concentration of wines, but that rootstocks did not have a consistent effect on the flavonoid content of scions. This difference might be attributed to differences in the environment, cultural practices and scion ( Oliveira et al, 2020 ). In our study, 1103P reduced the anthocyanin concentrations in wines, while 5A did not significantly affect the anthocyanin concentration of wine, consistent with the trend in grapes, suggesting that rootstocks could indeed affect anthocyanin concentrations in wine by altering anthocyanin concentrations in grapes.…”
Section: Resultsmentioning
confidence: 99%
“…The rootstocks used in this experiment have a certain genetic diversity and can therefore influence several physiological and biochemical grapevine aspects, which could have a reflection on wine composition and quality. Indeed, results of studies have shown effect of rootstocks on the grapevine physiology, biochemistry, wine biochemical profile, wine quality and wine sensory characteristics (Somkuwar et [36,25,26,29] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the rootstocks did not influence must from the other hybrids studied. The rootstock effect is more significant in terms of phenolic compounds on must since grapes from grapevines grafted onto 'IAC 572 Jales' showed higher concentrations of tartaric and malic acids, while those grafted onto '1103P' presented high levels of total phenols and nonflavonoids (Oliveira et al 2020). Hybrids with the highest bunch size showed a higher fruit maturation index because of low acidity in the must.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of rootstocks are available for grapevine use, and they are adapted for different edaphoclimatic conditions (Delrot et al 2020;Jin et al 2016;Troncoso et al 1999). The IAC has also developed new rootstocks, which exhibit high vegetative vigor and adaptability to acidity soil and they have shown high resistance to phylloxera and nematodes (Oliveira et al 2020). The most used rootstocks in the subtropical region of Brazil are 'IAC 766 Campinas' and 'IAC 572 Jales' (Mattar et al 2019).…”
Section: Introductionmentioning
confidence: 99%